2020
DOI: 10.4337/qmjip.2020.03.01
|View full text |Cite
|
Sign up to set email alerts
|

Patents and gender: a contextual analysis

Abstract: Patent law is considered to be an objective law, dealing with the objective subject matter of the ‘technical arts’. Yet, empirical studies show that patenting rates around the world are gendered. This article analyses the roots of the gender patent gap, and how this correlates to the invention and innovation processes. It shows that the gendered nature of the patent-regulated knowledge governance system forces women into traditionally male spaces and fields in order to partake in the extant patent game. Yet, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…As has been noted elsewhere, creation occurs in a complex ecosystem. 198 It is not a simple uni-directional stream. But, the patent system is only interested in the end-products of creation.…”
Section: Approaching the Event Horizonmentioning
confidence: 99%
“…As has been noted elsewhere, creation occurs in a complex ecosystem. 198 It is not a simple uni-directional stream. But, the patent system is only interested in the end-products of creation.…”
Section: Approaching the Event Horizonmentioning
confidence: 99%
“…That is, they pertain to socialised constructions of the scientist and the inventor, science and the inventive process, the patentable invention, and the entrepreneur, all of which are coded masculine (Burk, 2007(Burk, , 2011Rosser, 2009;Swanson, 2011). Furthermore, patenting is gendered because of gender-normative roles, biases and power dynamics (Lai, 2020).…”
Section: The Gendered Patentmentioning
confidence: 99%
“…Achieving gender balance in participation is not just a matter of social justice. Research has shown that the benefit of more equal participation is improved collective intelligence, [25] cognitive diversity in problem solving, [26] and more realistic understanding of context, [27] all of which help make research and innovation both relevant and responsible to society. Gender equality is today often connected to diversity (recognition of ethnicity, age, educational status, etc.…”
Section: Reflection On Gender Equality In Participationmentioning
confidence: 99%